2018
DOI: 10.1101/278945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation age acceleration and risk factors for Alzheimer’s disease

Abstract: (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 66 publications
6
7
0
Order By: Relevance
“…Our LD score regression analysis replicated the positive genetic correlations with central adiposity reported by Lu et al (2018) at nominal significance levels, supporting the suggestion that observed phenotypic associations (14,18) may result in part from a shared genetic aetiology. We did not, however, replicate previously reported correlations between Horvath-EAA and metabolic disease-related traits or diabetes, and found these traits to be correlated with Hannum-EAA at only nominal significance levels in our larger sample (19).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our LD score regression analysis replicated the positive genetic correlations with central adiposity reported by Lu et al (2018) at nominal significance levels, supporting the suggestion that observed phenotypic associations (14,18) may result in part from a shared genetic aetiology. We did not, however, replicate previously reported correlations between Horvath-EAA and metabolic disease-related traits or diabetes, and found these traits to be correlated with Hannum-EAA at only nominal significance levels in our larger sample (19).…”
Section: Discussionsupporting
confidence: 89%
“…A number of the genes significantly associated with Horvath-EAA are related to metabolism ( NHLRC1 , TPMT , KDM1B , and ESYT3 ), consistent with several studies reporting phenotypic associations between Horvath-based EAA and metabolic syndrome characteristics and supporting the suggestion of a role in tracking metabolic ageing (14,18). Others are involved in immune system pathways ( TRIM59 , KPNA4 , EDARADD ), while several have roles in cellular processes linked to ageing: apoptosis and autophagy ( FAIM ), ageing and autophagy ( TERT ), and coordinating vital cell functions ( PIK3CB ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations